The Vicar , the Nobleman, and the Peasant: About a Book and its Readers - Hansen, Henning (Mémoires du livre / Studies in Book Culture, 2022)
This article centres around a volume of sermons and its three documented owners. The book first belonged to a vicar, then to a nobleman, and finally to a farmhand. The three owners all left marks on the book, and the farmhand wrote a remarkable passage on its last page, detailing his reading of the book. The three owners’ possession of the book spans over a century, 1766–1876, a period that saw people’s reading habits and reading practices transform fundamentally. In this context Sweden, a forerunner in literacy development, constitutes a particularly interesting example. The journey that this book made provides an insight into provincial book culture and reading practices, and also tells us something about the literacy development of the time. Linking the reading practices to socioeconomic status, the article suggests that the habit of rereading lived on among uneducated readers in the countryside for quite some time.